Ngabeungkat Dawuan as Intangible Cultural Heritage: An Analysis of Ritual, Environmental Awareness, and Local Identity in the Perspective of Educational Management - Ahmad Fathoni; Abdul Basit; Slamet Pamuji (Universitas Nurul Jadid, 2025)
The growing disconnect between formal education, environmental sustainability, and local cultural knowledge highlights the need for context-based educational approaches. This study examines Ngabeungkat Dawuan as an intangible cultural heritage by analyzing its symbolic meaning, ecological function, social role, and relevance within educational management. Using a qualitative ethnographic design, data were collected through participant observation, in-depth interviews, and documentation in Dayeuhluhur, Cilacap Regency, and analyzed using an interactive model with triangulation to ensure credibility. The findings reveal that Ngabeungkat Dawuan functions as a holistic cultural system integrating spiritual values, environmental awareness, and social cohesion. The ritual positions water as both a vital resource and a sacred entity, while simultaneously operating as a community-based environmental management practice and an informal learning space for intergenerational knowledge transmission. It also strengthens collective identity and embeds ecological responsibility within social norms. This study contributes by integrating ritual, ecology, and educational management into a unified analytical framework, demonstrating that local traditions can serve as culturally grounded and environmentally oriented educational resources. The study concludes that Ngabeungkat Dawuan offers a relevant model for developing context-sensitive educational practices, although its integration into formal education requires institutional support and policy alignment.